Engineering of high yield production of L‐serine in Escherichia coli. Issue 4 (7th October 2015) - Mundhada, Hemanshu; Schneider, Konstantin; Christensen, Hanne Bjerre; Nielsen, Alex Toftgaard
ABSTRACT: L‐serine is a widely used amino acid that has been proposed as a potential building block biochemical. The high theoretical yield from glucose makes a fermentation based production attractive. In order to achieve this goal, serine degradation to pyruvate and glycine in E. coli MG1655 was prevented by deletion of three L‐serine deaminases sdaA, sdaB, and tdcG, as well as serine hydroxyl methyl transferase (SHMT) encoded by glyA . Upon overexpression of the serine production pathway, consisting of a feedback resistant version of serA along with serB and serC, this quadruple deletion strain showed a very high serine production yield (0.45 g/g glucose) during small‐scale batch fermentation in minimal medium. Serine, however, was found to be highly toxic even at low concentrations to this strain, which lead to slow growth and production during fed batch fermentation, resulting in a serine production of 8.3 g/L. The production strain was therefore evolved by random mutagenesis to achieve increased tolerance towards serine. Additionally, overexpression of eamA, a cysteine/homoserine transporter was demonstrated to increase serine tolerance from 1.6 g/L to 25 g/L. During fed batch fermentation, the resulting strain lead to the serine production titer of 11.7 g/L with yield of 0.43 g/g glucose, which is the highest yield reported so far for any organism. Biotechnol. Bioeng. 2016;113: 807–816. © 2015 Wiley Periodicals, Inc. Abstract : Escherichia coli was engineered for high yield production of L‐serine by deletion of the main serine degradation pathways and by overexpression of enzymes required for serine production. Tolerance towards L‐serine was increased by a combination of adaptive evolution and overexpression of a potential novel serine exporter. The resulting strain produces L‐serine by fed batch fermentation with the highest yield so far reached by any organism.